"Balancing Justice and Protection: The Presumption of Innocence and The Rights of Defense for Clerics Accused of Sexual Abuse of Minors Under Canon Law and Secular Law" - Kumar, Vanshika (Journal of Neonatal Surgery, 2025)
This paper will explore the dual legal frameworks under which clerics accused of sexual abuse of minors are judged: Canon Law and secular law. Focusing on the principles of the presumption of innocence and the rights of the defense, the paper will analyses how these principles are safeguarded within the Catholic Church’s internal judicial system (Canon Law) and compare them with the protections afforded under national and international secular legal systems. Key questions will include whether the Church’s ecclesiastical procedures align with global human rights standards, whether Canon Law offers adequate safeguards for accused clerics in a climate of public outrage, and how both legal systems address the tensions between the need for justice for victims and the rights of the accused.